THE EFFECT OF WALL DRILLS ON THE SPEED OF DOLLYO CHAGI KICKING IN JUNIOR TAEKWONDO ATHLETES AT THE TIGER SUMATERA DOJANG IN BINJAI - Cahaya Kamalin Mastura; Suprayitno; Siregar, Abdul Hakim; Nasution, Usman; Damanik, Saipul Ambri (Journal of Physical Education, Health and Sports Recreation, 2025)
This study aims to analyze the effect of wall drill training on increasing the speed of dollyo chagi kicks in Taekwondo athletes at Dojang Tiger Sumatera Binjai. The study was conducted in Binjai City, North Sumatra Province, from April 7 to May 7, 2025. The sample consisted of 10 athletes aged 15-17 years, consisting of 4 male athletes and 6 female athletes. Based on the results of the initial measurements (pre-test), all participants showed kick speeds that were in the category of less to very less, with an average value of 11.50. After being given treatment in the form of wall drill training for five weeks with a frequency of four times per week, a re-measurement (post-test) was carried out, and an average increase of 19.60 was obtained. To test the hypothesis, a paired sample t-test technique was used using SPSS version 26 software. The test results showed that the t-value was -11.732 with degrees of freedom (df) = 9 and a significance value (Sig. 2-tailed) = 0.000. This value compares with the t-table value of 2.262 (at a 5% significance level). Since t-test > t-table and p < 0.05, it can be concluded that there is a statistically significant difference between the pre-test and post-test scores. This means that wall drills significantly increased the speed of the dollyo chagi kick. This finding supports the effectiveness of wall drills as a functional training method that positively impacts kicking performance in Taekwondo athletes. Therefore, this training can be recommended as an efficient alternative training strategy for improving the speed aspect of the dollyo chagi technique.